Food Difficulties in Infancy and ASD: A Literature Review - Marios Vasilakis; Konstantinos Polychronis; Eleni Panagouli; Efthalia Tzila; Alexia Papageorgiou; Loretta Thomaidou; Theodora Psaltopoulou; Maria Tsolia; Theodoros N. Sergentanis; Artemis K. Tsitsika (MDPI AG, 2022)
Purpose: The aim of this literature review is to investigate the potential association between specific food difficulties and autism spectrum disorder (ASD) during the first two years of life. Materials: The search was conducted in PubMed, Google Scholar, Embase and PsycInfo databases. Results: Twenty-one studies were synthesized (3763 infants and children). Difficulties during breastfeeding, breast milk refusal and avoidance of taking solids have been linked to ASD. Infants with ASD have been referred to as picky eaters. Problematic mealtime behaviour during infancy has also been associated with ASD. Conclusions: The present review highlights the association between food difficulties, including problematic mealtime behaviours, food selectivity, breastfeeding difficulties and food refusal during infancy and ASD early during life, including the first months.